2020
DOI: 10.7717/peerj.9376
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and spoilage potential of microbial communities associated with grape sour rot in eastern coastal areas of China

Abstract: As a polymicrobial disease, sour rot decreases grape berry yield and wine quality. The diversity of microbial communities in sour rot-affected grapes depends on the cultivation site, but the microbes responsible for this disease in eastern coastal China, has not been reported. To identify the microbes that cause sour grape rot in this important grape-producing region, the diversity and abundance of bacteria and fungi were assessed by metagenomic analysis and cultivation-dependent techniques. A total of 15 bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…For example, we used PCR primers 338F/806R to amplify the 16S rRNA V3–V4 regions of bacteria and an Illumina MiSeq PE300 platform for sequencing. Similar results were obtained by amplifying the 16S rRNA V4 region using primers 515F/806R and sequencing on an Illumina HiSeq 2500 platform [ 27 ], or through amplifying the V6 hypervariable region of 16S rRNA and sequencing on a 454 Titanium platform [ 8 ]. In this study, Pantoea was found to have a significant positive correlation with a few categories of VOCs during fermentation, such as higher alcohols (straight-chain fatty alcohols in YC and QTX, and branched-chain fatty alcohols in YQY), esters (acetic esters, methyl esters, isobutyl esters and isoamyl esters in YQY, and acetic esters in QTX), and fatty acids in QTX.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…For example, we used PCR primers 338F/806R to amplify the 16S rRNA V3–V4 regions of bacteria and an Illumina MiSeq PE300 platform for sequencing. Similar results were obtained by amplifying the 16S rRNA V4 region using primers 515F/806R and sequencing on an Illumina HiSeq 2500 platform [ 27 ], or through amplifying the V6 hypervariable region of 16S rRNA and sequencing on a 454 Titanium platform [ 8 ]. In this study, Pantoea was found to have a significant positive correlation with a few categories of VOCs during fermentation, such as higher alcohols (straight-chain fatty alcohols in YC and QTX, and branched-chain fatty alcohols in YQY), esters (acetic esters, methyl esters, isobutyl esters and isoamyl esters in YQY, and acetic esters in QTX), and fatty acids in QTX.…”
Section: Discussionsupporting
confidence: 62%
“…Regarding the most abundant bacteria, microorganisms from the genus Pantoea were detected in all the sub-regions, enriched in QTX samples, and rapidly dominated the population after fermentation initiation ( Figure 5 a). Studies have shown that Pantoea is also a key feature in other wine regions, such as Penglai, Yangling, Shanshan, Yanqi, Heshuo, Huoerguosi, Fukang, and Manasi in China [ 25 , 27 ]; Minho, Douro, Dão, Bairrada, Estremadura, and Alentejo in Portuguese [ 8 ]; Modra in Slovakia [ 47 ]; Central Pennsylvania in the United States [ 48 ]; moreover, the Ullum Valley of San Juan Province in Argentina [ 49 ]. The predominant presence of this group is independent of the identification methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…vinifera which is discussed in this paper. The diversity and abundance of sour rot pathogenic fungus have been analyzed through metagenome analysis and cultivation related techniques . It was found that 3 polygalacturonase genes related to pathogenesis and 814 genes encoding guazatine resistance-related genes were obtained by genome sequencing and transcriptome analysis of G.…”
Section: Discussionmentioning
confidence: 99%
“…The diversity and abundance of sour rot pathogenic fungus have been analyzed through metagenome analysis and cultivation related techniques. 42 It was found that 3 polygalacturonase genes related to pathogenesis and 814 genes encoding guazatine resistance-related genes were obtained by genome sequencing and transcriptome analysis of G. citri-aurantii from citrus. 43 In this study, the grape sour rot fungus was identified to be similar to Geotrichum candidum, with 85.97% inter-sequence similarity, which was similar to a previous report.…”
Section: ■ Discussionmentioning
confidence: 99%